Surgical explant of a right ventricular assist device with sternum-sparing technique. (22nd December 2019) - Monteagudo-Vela, Maria; Panoulas, Vasileios; Riesgo-Gil, Fernando; Simon, Andre
Abstract: The use of long-term mechanical assist devices for isolated right ventricular failure is rare. Herein, we describe our protocol for successful recovery of the right ventricle and subsequent explantation of a right ventricular assist device using a sternum-sparing technique and insertion of a titanium plug to occlude the coring defect of the inflow cannula.